Microstructure and scratch behavior of TiB/Ti-6Al-4V composites fabricated by wire-feed electron beam additive manufacturing; Materials Letters; Vol. 405 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Shugurov A. R. Artur Rubinovich; Pribytkov G. A. Gennady Andreevich; Krukovsky K. V. Konstantin Veniaminovich (2026, 2026)
Title screen